2014
DOI: 10.1186/1471-2393-14-286
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perception of decreased fetal movements from maternal and fetal perspectives, a cohort study

Abstract: BackgroundMaternal counting of fetal movement is a popular and valuable screening tool of fetal wellbeing, however it is still not known what percentage of healthy pregnant women who gave birth to healthy term newborns had experienced decreased fetal movements during gestation and what maternal and fetal factors are associated with this maternal perception of decreased fetal movements. The aim of this study was to assess the associations between maternal perception of decreased fetal movements and maternal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Perception of fetal movements is affected by multiple influences; equally, the perception of RFM is very common . These, together with the very modest risks of markers of placental dysfunction in women with repeated episodes, and the contradictory data on birthweight, suggest that recurrent RFM is likely to be a poor discriminator of pregnancy risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perception of fetal movements is affected by multiple influences; equally, the perception of RFM is very common . These, together with the very modest risks of markers of placental dysfunction in women with repeated episodes, and the contradictory data on birthweight, suggest that recurrent RFM is likely to be a poor discriminator of pregnancy risk.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, RFM is a common symptom in pregnancy and reason for access to emergency care: approximately 8%‐17% will present, and the incidence of fetal demise or compromise at presentation is low . There is, however, the capacity to do harm, either by causing increased maternal anxiety or through obstetric intervention, by using resources, or by iatrogenic preterm or early term birth.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review shows that fetal/maternal factors such as obesity, anterior placenta, malpresentation, liquor abnormalities, smoking, and primiparity are all associated with increased prevalence of RFM among pregnant women. 8 We must recognize these factors in order to recognize false positives and thus Poojari VG et al Int J Reprod Contracept Obstet Gynecol. 2018 Jan;7(1):88-93 International Journal of Reproduction, Contraception, Obstetrics and Gynecology Volume 7 · Issue 1 Page 92 provide reassurance as well as to prevent unnecessary interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, twothirds of the studied women knew that sounds, fetal sleep pattern and maternal activity level affect their perception of fetal movement and most of them knew that smoking and medications affect their perception of fetal movements. The woman's perception of fetal movements is influenced by sounds, drugs, cigarette smoking, fetal sleep state, time of the day, maternal activity level, the presence of obesity, maternal employment, parity, placental position, maternal fasting, and maternal position during counting (29,34,35) . The total knowledge score regarding fetal movement in the present study revealed that about two-thirds of the women had a fair knowledge and only thirty-one women (10.3%) had good knowledge regarding fetal movement.…”
Section: Discussionmentioning
confidence: 99%